(untitled) (Annals of Medical Research, 2023)
Aim: Mental health of the seasonal agricultural workers (SAW) can be negatively affected due to working under hard conditions, being exposed to discrimination from time to time, working in a socially isolated field, and having insufficient social support resources. This study aimed to assess the mental health of the SAW. Materials and Methods: This study was conducted from June to September 2021 in a family health center region in a province located in the southeast of Turkey in which the SAW intensely populated. The study sample consisted of 300 seasonal agricultural workers. Data were collected using an introductory form and the Brief Symptom Inventory (BSI) through face-to-face interviews. The data were analyzed using the Statistical Package for Social Sciences (SPSS) 22.00 program, descriptive statistics (numbers, percentages, means), independent samples t-test, the Mann Whitney-U test, variance analysis, and the Kruskal-Wallis test. Results: The participants’ mean subscale scores were 8.08±6.39 for somatization, 15.81±9.15 for depression, 11.79±8.32 for anxiety, 8.84±5.18 for hostility, and 14.10±8.13 for negative self-concept. Their mean index scores were 1.10±0.58 for the Global Severity Index (GSI), 24.44±11.09 for the Positive Symptom Total (PST), and 2.08-0.53 for the Positive Symptom Distress Index (PSDI). A statistically significant difference was found between anxiety and depression subscales by gender; somatization subscale by marital status, education level, presence of chronic diseases, and duration of employment; and negative self-concept and hostility subscales by presence of chronic diseases (p<0.05). Conclusions: It can be concluded that the SAW had psychopathological tendencies. Therefore, it is critical to periodically assess the mental health of the SAW and to develop coping strategies regarding the problems they experience.